2012
DOI: 10.1016/j.jpsychores.2011.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic growth in coronary artery disease outpatients: Relationship to degree of trauma and health service use

Abstract: Greater PTG was related to greater objective risk of morbidity but not actual morbidity, suggesting that contemplation about the risk of future health problems may spur PTG. Moreover, greater PTG was associated with seeking non-urgent healthcare. Whether this translates to improved health outcomes warrants future study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 44 publications
3
35
0
1
Order By: Relevance
“…This link between diagnosis appreciation and motivation of growth is consistent with the findings by Leung et al (2012), who concluded that perceived risk of future health problems commonly instigates PTG: … I just thought that I could have died or become really ill without realising I didn’t have anything wrong with me and that really scared me. But then I thought ‘gee I’m so glad that they found it, I’m really lucky because I have another chance here’.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…This link between diagnosis appreciation and motivation of growth is consistent with the findings by Leung et al (2012), who concluded that perceived risk of future health problems commonly instigates PTG: … I just thought that I could have died or become really ill without realising I didn’t have anything wrong with me and that really scared me. But then I thought ‘gee I’m so glad that they found it, I’m really lucky because I have another chance here’.…”
Section: Resultssupporting
confidence: 88%
“…This meaning-making process is important at the time of diagnosis with a high frequency of people interpreting such events as traumatic as they face mortality issues and identity crises (Bostock et al, 2009). Current research in the area of adverse events, which encompasses major surgeries like CABG, is progressing from the mere understanding how people adapt and adjust to a traumatic event (Bostock et al, 2009; Sheikh, 2004) to the understanding of potential of psychological benefits and personal growth following CABG surgery (Ai et al, 2013; Leung et al, 2012). …”
mentioning
confidence: 99%
“…42 Post-traumatic growth is a likely, yet understudied, indicator of successful adaptation to the cancer experience 38 and may represent a resource for optimizing health behaviors. [43][44][45][46] For example, after treatment, a brief strengthsbased case-management intervention targeting health care SE/activation and post-traumatic growth may provide a motivating narrative for CCS to engage in cancer-related follow-up care. Developing these and other tailored interventions based on patient resources/characteristics for longterm engagement with care may mitigate subsequent declines in follow-up care.…”
Section: Discussionmentioning
confidence: 99%
“…These connections may also be understood within the framework of post-traumatic growth, the concept of positive consequences arising as a result of coping with traumatic experiences, such as serious medical illness (Sheikh, 2004; Leung et al, 2012). While our findings regarding positive emotional states and health behaviors may be related to this phenomenon, we found that that positive states and health behaviors also appeared to be connected even prior to the cardiac event, suggesting another possibility: those who have optimism/positive affect at any timepoint may be more likely to take on heart-healthy behavior, and interventions may wish to focus on cultivating these states rather than necessarily focusing on post-traumatic growth.…”
Section: Discussionmentioning
confidence: 99%